Will vaccine hesitancy compromise our efforts to face the next SARS-CoV-2 epidemic wave? - Laura Sticchi; Lucia Taramasso; Antonio Di Biagio; Dario Olobardi; Giancarlo Icardi; Matteo Bassetti (Taylor & Francis Group, 2021)
We have checked the vaccination history of 389 elderly patients (62.9% males, mean age of 78.5 + 8.4 years) hospitalized for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. Information regarding pneumococcal vaccination was available for 354 patients (91.0%): the overall vaccination coverage rate (VCR) was 19.8% (70/354), 11.3% received only 13-valent pneumococcal conjugate vaccine (PCV13), 3.4% were immunized with 23-valent pneumococcal polysaccharide vaccine (PPSV23), 5.1% received both vaccines. VCR among the elderly population in Liguria Region was 26.2% (118,581/453,082), among them 13.7% received PCV13, 12.4% were immunized with at least one dose of PPSV23. Regarding the 2019-2020 influenza season vaccination data were available for 46 patients: 59% of them were immunized. VCR in the elderly population was 51.7% (234,153/453,082).